Answer:
x=-1 and y=-9
Explanation:
So the equations are 7x-3y=20 and y=5x-4
the second equation gives you a value that you can substitute in for y
sub for y in the first equation:
7x-3(5x-4)=20
distribute the 3 to the values in the parenthesis
7x-15x+12=20
combine like terms
-8x+12=20
subtract 12 from both sides
-8x=8
divide both sides by -8
x=-1
Now that you have your x value you should sub it into one of the equations to get the y value, we will sub it into the first equation
7(-1)-3y=20
multiply
-7-3y=20
add 7 to both sides
-3y=27
divide both sides by -3
y=-9
Substitute the values in to check your work
7(-1)-3(-9)=20
-7+27=20
20=20
correct, now the other equation
(-9)=5(-1)-4
-9=-5-4
-9=-9
correct